Telepsychiatry and mental health equity in correctional facilities: Legal opportunities and challenges - Patrinos, Dimitri (Lex Electronica)

(untitled) (Centre de recherche en droit public Université de Montréal, 2023)
Lack of access to mental health care in Canadian correctional facilities is a serious and longstanding issue. Telepsychiatry, which entails the usage of information and communications technologies to provide remote mental health care to patients, has been demonstrated to be an effective model of mental health care provision in correctional facilities. The right to health care, including mental health care, of inmates is recognized in both international and domestic law. However, mental health conditions remain suboptimal in Canadian correctional facilities and are far below the standards which exist in the general community, leading to significant mental health disparities for inmates. Telepsychiatry can be viewed as a vector for increasing mental health equity in the correctional system and provides a promising opportunity for correctional facilities to meet their legal obligations to provide inmates with health care, including mental health care. This article explores the legal frameworks governing the provision of mental health care services in Canadian correctional facilities and highlights the role telepsychiatry can play in the fulfillment of these legal frameworks. It also explores the legal challenges facing the implementation of telepsychiatry in correctional facilities. Ultimately, despite these challenges, it argues that telepsychiatry should be more widely implemented in correctional facilities to ensure mental health equity for inmates.